Grazing intensity on herbage production of irrigated tanzania grass pasture during the spring and summer - Martha Júnior, Geraldo Bueno; Corsi, Moacyr; Barioni, Luis Gustavo; Vilela, Lourival (Pesquisa Agropecuaria Brasileira, 2004)
This experiment aimed to determine the effect of grazing intensity in irrigated Panicum maximum cv. Tanzania on forage production components. A randomized complete block design with four replicates, following a repeated measure arrangement, was used. In the plots, the effect of post-grazing residues (1,210, 3,036 and 5,471 kg/ha of green dry matter – GDM) on forage production components during the spring and summer was tested and, in the subplots, the effect of length of regrowth (9, 18 and 27 days after nitrogen fertilization) was studied. Total herbage dry mass, green herbage dry mass (leaves+stems) and leaf dry mass linearly increased (P<0.05) with increasing residual stubble mass or days of regrowth. A significant interaction (P<0.05) between length of regrowth and post-grazing residue was observed for stem dry mass in both seasons. During the summer, the leaf/stem ratio decreased with increasing post-grazing residue, but in the spring, the interaction between regrowth period and post-grazing residue was significant. The quantity of dead material increased with the length of regrowth. The residual stubble mass for irrigated, N-fertilized Tanzania grass pasture, during the spring and summer, considering a 36-day grazing cycle, should be around 1,650 to 2,700 kg/ha of GDM to ensure that leaf production and leaf/stem ratio be close to the maximum.